The Civil War diary quilt : [121 stories and the quilt blocks they inspired] - Youngs, Rosemary (Iola, Wis. : Kp Books, 2005)
Authentic diary entries of 10 women living during the Civil War along with 121 full-size quilt blocks inspired by the diary entries.
Subtitle from cover.
Keywords: United States -- History -- Civil War, 1861-1865.; Quilting -- Patterns; United States -- History -- Civil War, 1861-1865 -- Women; United States -- History -- Civil War, 1861-1865 -- Personal narratives; United States -- History -- Civil War, 1861-1865 -- Social aspects; Women -- United States -- Biography; Quilts -- United States -- History -- 19th century; Quilting -- Handbooks, manuals, etc